Socio-economic inequality in Scottish education - James Lester; Andrew McKendrick; Luke Sibieta (Institute for Fiscal Studies (IFS), 2023)
The next wave of Programme for International Student Assessment (PISA) data will be published in December 2023. This will relate to PISA tests taken in 2022, the first wave of data after the COVID-19 pandemic. In advance of these new data, this report seeks to take stock of performance to date in Scotland, including trends in reading, maths and science scores over time and the socio-economic gap in scores, as well as how performance in Scotland compares with other UK nations in particular.
Keywords: 330; Education and skills; Poverty; inequality and social mobility; Education; Inequality; Northern Ireland; Schools; Scotland; Wales; Northern Ireland